Archaism in Mandailingese - Lubis, Syahron; Hasibuan, Namsyah Hot (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
The aim of the present study is to investigate and record archaic words and expressions in Mandailingese, an ethnic language spoken in the Regency of Mandailing Natal, North Sumatra. The design of this study is qualitative-descriptive, in which the data were collected by interviewing eight native-speaker informants and by examining some old written texts of Mandailingese culture. The results of the study show that there are approximately 350 archaic words and expressions found and recorded. They are categorized into nouns, verbs, adjectives, and adverbs.